Wat Amsterdam betreft. - Barents, Els; Beeren, W.A.L.; Bloem, Marja; Crommelin, Liesbeth; Dippel, Rini; Driessen, Hendrik; Imanse, Geurt; Kras, Reyer; Mignot, Dorine; Petersen, Ad; Pieters, Din; Plantenga, Haro; et al. (Amsterdam : Stedelijk Museum Amsterdam, 1985)
Aarntzen, Jan ; Abramovic, Marina & Ulay ; Anema, Taco ; Appenzeller, Hans ; Armando ; Bannenberg, Peggy ; Bastiaans, Christiaan ; Beeke, Anthon ; Bijl, Guillaume ; Blanca, Paul ; Blom, Ansuya ; Bloom, Barbara ; Blotkamp, Carel ; Boersma, Pieter ; Bogaerts, André ; Brethouwer, Harmen ; van den Broeck, Frank ; Buisman, Sjoerd ; Byron, Michael ; Cassée, Dick ; de Châtel, Krisztina ; Clemente, Francesco ; Colombine ; Colton, Adam ; Commandeur, Jan ; Constant ; Content, Eli ; Daniëls, Pauline ; van Denderen, Ad ; Dibbets, Jan ; Diederen, Jef ; Dieleman, Piet ; Dieperink, Menno ; Diepraam, Willem ; Domburg, Bart ; Drupsteen, Jaap ; Dumas, Marlene ; van Elk, Ger ; van Elk, Ria ; Elzas, Jaap ; Escher, Gielijn ; Fortuyn/O'Brien ; Freijmuth, Alphons ; Frijns, Bert ; Garcia, David ; De Groot, Kees ; de Groot, Pauline ; Gudmundsson, Sigurdur ; Hamilton, Richard ; van Hemert, Frank ; Henneman, Jeroen ; Heyboer, Anton ; Heyink, Harry ; Hoek, Klaas ; Hoover, Nan ; Hooykaas, Madelon ; van der Horst, Loes ; Jansen, Jan ; de Jonge, Jaap ; Jongema, Marten ; Kemps, Niek ; Kiefer, Anselm ; Klaarenbeek, Frits ; Klashorst, Peter ; Kodde, Gerard ; van Koningsbruggen, Rob ; de Kop, David van ; Lap, Geert ; Lataster, Ger ; Lichtveld, Alexander ; Long, Richard ; Lucassen ; van Manen, Hans ; Mantje, Aldert ; Mechanicus, Philip ; Meitner, Richard ; Mijksenaar, P.J. ; Mol, Pieter Laurens ; Moritz, Ulf ; Müller, Paul ; Neuteboom, Boudewijn ; Nienhuis, Bert ; de Nooijer, Paul ; Oudendijk, Sonja ; Ploeg, Maarten ; Postma, Hannes ; Reyers, Steven ; Roeland, Jan ; Rogge, Cornelius ; Rubin, Anna ; Sanders, Willem ; van Santen, Joost ; Schippers, Wim T. ; Scholte, Rob ; Schouten, Marien ; Schuil, Han ; Servaas ; Sierhuis, Jan ; Singels, Han ; Sipek, Borek ; Sluik/Kurpershoek ; Smit, Robert ; etc.
biog. per kunstenaar
Wat Amsterdam betreft... / As far as Amsterdam goes...., Stedelijk Museum Amsterdam, 22.11.'85 - 5.1.'86
Nederlands & Engels
boek
Keywords: Amsterdam